Recordando John Milton (1608-1674) - Ribeiro, Nuno (Via Panoramica: Revista de Estudos Anglo-Americanos / A Journal of Anglo-American Studies, 2020)
This text is a very general note on the work and life of John Milton (1608-1674), having Paradise Lost and the context of the creation of the writer’s major work at its core. It tries to put on view a cursus poeticus revealed at the very first stages of his creation, then corroborated as the expression of a sense of mission joining the poet and the polemicist in the service of the good old cause. Paradise Lost should not be seen as just a venerable monument or canonical achievement: the long narrative poem is also a pièce de résistance and a vivid document in culture. A brief reference to Samson Agonistes and Paradise Regained, the last moments of an acclaimed literary legacy, closes the text.